A novel force transduction pathway from a tension sensor to the gate in the mechano-gating of MscL channel - Sawada, Yasuyuki; Nomura, Takeshi; Martinac, Boris; Sokabe, Masahiro (Frontiers in Chemistry, 2023)
The bacterial mechanosensitive channel of large conductance MscL is activated exclusively by increased tension in the membrane. Despite many proposed models for MscL opening, its precise mechano-gating mechanism, particularly how the received force transmits to the gate remains incomplete. Previous studies have shown that along with amphipathic N-terminus located near the cytoplasmic surface of the membrane, Phe78 near the outer surface also acts as a “tension sensor”, while Gly22 is a central constituent of the “hydrophobic gate”. Present study focused on elucidating the force transmission mechanism from the sensor Phe78 in the outer transmembrane helix (TM2) to the gate in the inner transmembrane helix (TM1) of MscL by applying the patch-clamp and molecular dynamics (MD) simulations for wild type MscL and its mutants at the sensor (F78N), the gate (G22N) and their combination (G22N/F78N). F78N MscL resulted in a severe loss-of-function, while G22N MscL caused a gain-of-function channel with spontaneous openings at the resting tension. We initially speculated that the spontaneous opening in G22N mutant might happen without tension sensing at Phe78. To test this hypothesis, we examined the double (G22N/F78N) mutant, but unexpectedly it showed neither spontaneous opening nor opening even at a relatively high tension in the membrane. To understand the underlying mechanism, we conducted MD simulations and analyzed the force transmission mechanism. Results showed that the mutation at the tension sensor (F78N) in TM2 caused decreased interaction not only with lipids, but also with a group of amino acids (Ile32-Leu36-Ile40) in the neighboring TM1, resulting in an inefficient force transmission to the gate-constituting amino acids on TM1. This change also induces a slight tilting of TM1 towards the membrane plane and decreases the size of the gate, which seems to be the major mechanism for the inhibition of spontaneous channel opening in the double mutant. More importantly, the newly found interacting site between TM2 (Phe78) and adjacent TM1 (Ile32-Leu36-Ile40) helices seems to be an essential force transmitting mechanism for the stretch-dependent activation of MscL given that substitution of any one of these 4 amino acids with Asn resulted in severe loss-of-function MscLs in our previous work.